Pour une géographie des courses à pied en France - François Madoré (Unité Mixte de Recherche 8504 Géographie-cités, 2021)
Running has been developing rapidly in France for several decades, and this practice is accompanied by an increase in the number of sporting events in many areas. However, the geographical logics behind the spatial diffusion of the phenomenon have never been analyzed. This article therefore begins by reviewing the reasons for the development of this phenomenon, before presenting the method used to build the first geographic database of running events in France, which then allows us to draw the characteristic features of this geography on the scale of the French territory. A multiple linear regression shows that the most rural departments tend to have a higher density of running, particularly those located in the southern half of the hexagon, which is also more mountainous, and thus not unrelated to the much more pronounced growth of nature trails than road races. Finally, if this regression model only explains a little more than half of the variance, it is perhaps because the ubiquity of the running phenomenon is such that it results in a very wide spatial coverage, albeit unequal in terms of density, so much so that running has become an event of territorial animation, including in many small towns.